Navigating Hybrid Organizations: Bridging Governance Gaps in Healthcare Policy Implementation in Indonesia - Rulinawaty, Rulinawaty; Samboteng, Lukman; Andriyansah, Andriyansah; Kasmad, M. Rachmat; Alwi, Alwi; Mutmainnah Basit, Mutmainnah Basit (Faculty of Science and Technology University of Pramita Indonesia, 2025)
Effective healthcare policy implementation is critical for achieving universal healthcarecoverage. This study evaluates the implementation of Indonesia's National Health Insurance Program (Jaminan Kesehatan Nasional - JKN), aiming to identify significant regional variations and underlying factors influencing policy effectiveness. A qualitative case study approach was adopted, employing semi-structured interviews, focus group discussions, and document analysis across selected Indonesian regions. Findings indicate substantial discrepancies in policy implementation outcomes, primarily driven by institutional capacities, governance quality, administrative complexities, resource constraints, and varying levels of community engagement. The discussion highlights the necessity of addressing institutional fragmentation, improving governance mechanisms, and strengthening stakeholder collaboration to overcome existing barriers. This research underscores the importance of context-specific strategies and contributes to a deeper understanding of healthcare policy implementation challenges. The insights offer valuable guidance for policymakers and suggest areas for further investigation into governance improvements and region-specific implementation frameworks.